(untitled) (Journal of Global Arts Studies, 2025)
Background: In recent years, with the advancement of science and technology, the process of popularization and application of artificial intelligence (AI) technology has been accelerating, and it is empowering various fields. AI has exerted an extremely significant and far-reaching impact on the creation of traditional Chinese painting. Objective: The main objective of this thesis is to analyze the advantages and limitations brought by AI-empowered traditional Chinese painting creation. Methods: The research method of this paper is to explore the advantages and limitations of AI-empowered traditional Chinese painting creation by analyzing both the external visual dimensions and the internal spiritual dimensions of traditional Chinese painting. Results: What distinguishes this paper from previous studies is that it presents a relatively objective discussion on the advantages and limitations of AI-enabled Traditional Chinese Painting creation. Conclusion: The creation of traditional Chinese painting empowered by AI has been enhanced in such visual aspects as composition and modeling. However, its limitations are also quite prominent in the expression of spiritual dimensions.